Detection of Gallbladder Carcinoma Incidentally After Laparoscopic Cholecystectomy for Cholelithiasis, in a Tertiary Level Hospital - Sikder, Md Alamgir Hossain; Hasan, Fahim; Rahman, Shahidur; Naser, Jamal Abu (Journal of Dhaka National Medical College & Hospital, 2022)
Background: Carcinoma of gallbladder is a rare disease but extremely variable by geographical region and racial-ethnic group. The incidence of intra or postoperative incidental carcinoma of gallbladder diagnosed is estimated 0.2 and 2.8. Objective: To detect incidental gallbladder carcinoma after laparoscopic cholecystectomy & to correlate it with age variable and findings of gallbladder pathology postoperatively. Methods: A total 960 patients of gallbladder stone/cholelithiasis were carried out laparoscopically by laparoscopic cholecystectomy in the Department of Surgery of Dhaka National Medical College Hospital retrospectively during the period from January 2017 to December 2020. Results: Incidental gallbladder carcinoma were diagnosed in 3(0.41%) out of 960 patients undergone laparoscopic cholecystectomy. Conclusion: Gall bladder carcinoma is rare disease with poor prognosis. The use of meticulous laparoscopic technique seems to be important for the diagnosis and avoidance of early complication of the disease and microscopic examination is very much important for the depth of invasion, range of mucosal spread and lympho-vascular involvement. J. Dhaka National Med. Coll. Hos. 2022; 28 (01): 07-09